Modelamiento de relé virtual basado en teoría de cantidades incrementales (2017)
"The main purpose of this project is to model an incremental quantities based relay in National Instruments software: LabVIEW. Furthermore, relays behavior must be validated in different simulation scenarios, in order to confirm the protection time improvement between incremental quantities theory (time paradigm) and other standard methods (frequency paradigm). Additionally, as part of the projects objectives, the relay must implement the distance protection function and the theory limitations must be analyzed".-- Tomado del Formato de Documento de Grado.